2008
DOI: 10.1093/ajcn/88.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma carotenoids with risk factors and biomarkers related to cardiovascular disease in middle-aged and older women

Abstract: In middle-aged and older women free of CVD and cancer, plasma carotenoids were associated with smoking, obesity, LDL cholesterol, HDL cholesterol, Hb A(1c), and CRP. The associations differ among individual carotenoids, possibly reflecting metabolic effects of lifestyle and physiologic factors on plasma carotenoids, and may partially explain the inverse association of plasma carotenoids with CVD outcomes observed in epidemiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 52 publications
12
62
0
Order By: Relevance
“…Vasankari et al (28) showed that - The plasma concentrations of major carotenoids showed inverse and significant associations with CRP and IL-6 levels. The findings are in line with previous population-based studies reporting inverse associations between carotenoids in plasma and CRP after adjustment for confounding factors like dietary intake and smoking (15)(16)(17)(18)(19)(20)(21). Various explanations have been given, such as the consumption of circulating carotenoids during the neutralization of free radicals or depletion from blood due to an increased uptake by immune cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Vasankari et al (28) showed that - The plasma concentrations of major carotenoids showed inverse and significant associations with CRP and IL-6 levels. The findings are in line with previous population-based studies reporting inverse associations between carotenoids in plasma and CRP after adjustment for confounding factors like dietary intake and smoking (15)(16)(17)(18)(19)(20)(21). Various explanations have been given, such as the consumption of circulating carotenoids during the neutralization of free radicals or depletion from blood due to an increased uptake by immune cells.…”
Section: Discussionsupporting
confidence: 91%
“…Among individual carotenoids, only -carotene still showed a weak but significant association with CRP during treatment. The findings are in agreement with several large population-based studies showing that, among carotenoids, -carotene have the strongest relationship with inflammatory markers (15,16,18,21). In a previous study, we measured a panel of lipophilic antioxidants in patients with coronary artery disease, many of whom were receiving long-term statin treatment, and found that inflammatory activity was inversely associated with serum -carotene but not with lycopene or other antioxidants (17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Likewise, the correlation between plasma carotenoids and lipoproteins, in particular HDL cholesterol, was an expected finding that may reflect the role of lipoproteins in the storage or transport of carotenoids. In line with other studies [11][12][13][14][15][16][17], we also found an inverse association between plasma carotenoids and hypertension but neither blood pressure levels nor antihypertensive medication use remained as independent determinants after adjustments. The lower carotenoid levels among statin users was an expected finding.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, age, sex, excess weight, hypertension and smoking have been shown to correlate with carotenoid levels in the circulation [11][12][13][14][15][16][17]. Moreover, an inverse association between plasma carotenoids and systemic inflammation was a consistent finding in these studies [11][12][13][14][15][16][17]. In this respect, Creactive protein (CRP) has been the most studied marker, but interleukin (IL)-6 has also been assessed [15].…”
Section: Introductionmentioning
confidence: 92%